Etika Lingkungan Perspektif al-Qardhawi dan Said Nursi Studi Kasus Penambangan Batu di Padang Luas Kabupaten Kampar - Nurpadila, Fitri; Wilaela, Wilaela; Sukiyat, Sukiyat (Kutubkhanah, 2025)
This article discusses Environmental Ethics according to intellectual figures Yusuf al-Qardhawi and Badiuzzaman Said Nursi which are associated with the case of stone mining activities in Padang Luas Kampar Village, Riau. This natural exploitation practice has been going on since the beginning of the 21st century by certain parties there. Previously there was no mining, so the condition of the surrounding environment, the banks along the Kampar River were very beautiful and could be used by the community for various daily activities, such as bathing, washing, transportation. This qualitative research uses interview techniques with informants, observation at the mining site and documentation to obtain data. The stages of analysis are reduction, writing and drawing conclusions to answer the research problems. The research findings show that stone mining activities are still seen from the economic aspect and productive activities. On the other hand, there are changes in the natural environment such as mining activities that are getting closer to residential areas and even widening so that community land is bought by miners and becomes a stone mining area. The impact is not only the banks of the Kampar River which are getting wider and landslides, but also the collapse of houses due to landslides such as the case that occurred in Gobah Village